Evaluation of the ESGE recommendations for COVID-19 pre-endoscopy risk-stratification in a high-volume center in Germany - Zellmer, Stephan; Ebigbo, Alanna; Kahn, Maria; Muzalyova, Anna; Classen, Johanna; Grünherz, Vivian; Temizel, Selin; Dhillon, Christine; Messmann, Helmut; Römmele, Christoph (Endoscopy International Open, 2021)
Background and study aims The European Society of Gastrointestinal Endoscopy (ESGE) has defined COVID-19 infection prevention and control strategies within the endoscopy unit. These include pre-endoscopic questionnaire-based risk-stratification as well as pre-procedure viral testing. Real-life data on the effectiveness of these measures are presented here.Patients and methods Data from the outpatient endoscopic unit of the University Hospital Augsburg between July 1, 2020 and December 31, 2020 including the second pandemic wave were reviewed retrospectively. All patients were assessed with a pre-endoscopic risk-stratification questionnaire as well as viral testing using an antigen point-of-care test (Ag-POCT) in conjunction with a standard polymerase chain reaction (PCR) test. Highly elective procedures were postponed. The theoretically expected number of SARS-CoV-2-positive patients was simulated and compared with the actual number. In addition, endoscopy staff was evaluated with a rapid antibody test to determine the number of infections among the personnel.Results In total, 1029 procedures, 591 questionnaires, 591 Ag-POCTs, and 529 standard PCR tests were performed in 591 patients. 247 procedures in 142 patients were postponed. One Ag-POCT was positive but with a negative PCR test, while one PCR test was positive but with a negative Ag-POCT. This was lower than the theoretically expected number of COVID-19-positive patients (n = 15). One of 43 employees (2.3 %) in the outpatient endoscopy unit was seropositive.Conclusions Pre-endoscopic risk management including questionnaire-based risk stratification and viral testing seems to be an effective tool in combination with personal protective equipment for SARS-CoV-2 infection prevention and control within the endoscopy unit even in a high-prevalence setting.